2012
DOI: 10.1002/jsfa.4735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixing time, freeze-drying and baking on phenolics, anthocyanins and antioxidant capacity of raspberry juice during processing of muffins

Abstract: Despite the reduction in valuable compounds, muffin is a vehicle for the delivery of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…) and also in the total phenols of baked muffins enriched with red raspberry juice (Rosales‐Soto et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…) and also in the total phenols of baked muffins enriched with red raspberry juice (Rosales‐Soto et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of infrared drying and microwave drying has been applied in the dehydration of peach (Wang and Sheng 2006). Convective drying (Ljubinko et al 2012), freeze drying (Sablani et al 2011;Rosales-Soto et al 2012) and microwave vacuum drying (Bórquez et al 2010;Yanqiu et al 2013) are found to be used for raspberry dehydration. However, the infrared radiation and microwave vacuum combined drying (IR-MVD) characteristics and quality of raspberry were never reported.…”
Section: Introductionmentioning
confidence: 99%
“…The improved antioxidant properties of the CP‐enriched muffins were presumably due to the incorporation of compounds with strong antioxidant activity – mainly anthocyanins, where cyanidin‐3‐ O ‐rutinoside was predominant. Comparing the stability of anthocyanin compounds in baked muffins, Rosales‐Soto et al observed extremely small concentrations of these bioactive compounds in muffins enriched with raspberry juice, as compared to raspberry juice alone. These authors also pointed that this may result from poor stability and thermal degradation of the anthocyanins during baking.…”
Section: Discussionmentioning
confidence: 99%
“…Muffins rank third in popularity among breakfast products and attract a broad range of consumers . However, foodstuffs with high energy density and low nutrient values, such as muffins, cannot be recommended from a nutritional point of view to be eaten every day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation